Association between physical activity and online sexual objectification experience: The mediating role of body-image depression - Du, Xiang-Yu; Wang, Lin; Zuo, Yi-Fan; Wu, Qing; Qian, You-Ling; Ma, Rui (Frontiers in Psychology, 2023)
Objective: With the popularization and development of online media technology, more and more women are paying attention to their body image and physical behavior. The purpose of this study was to investigate the effect of online sexual objectification experience on the physical activity of female college students and verify the mediating role of body-image depression between them. Methods: A cross-sectional convenient sample of 882 female college students from four universities in Hubei Province completed an online survey, and the Online Sexual Objectification Experience Scale (OSOES), the Body-Image Depression Questionnaire, and the Physical Activity Rating Scale (PARS) were used to collect the data. The mediating effect of the association between online sexual objectification experience and physical activity, was examined using the process procedure in SPSS and the bootstrap method. Results: Online sexual objectification experience was significantly positively correlated with physical activity (r=0.420, p<0.01). Body-image depression was significantly negatively correlated with online sexual objectification experience and physical activity (r=-0.484, p<0.01; r=-0.569, p<0.01). Online sexual objectification experience can affect physical activity directly (β=6.49, p<0.001, effect value 44.97%) and also indirectly through body-image depression (β=7.95, p<0.001, effect value 55.03%); there were significant differences between major and education-level categories in body-image depression and physical activity. Conclusions: Both online sexual objectification experience and body-image depression can promote physical activity among female college students, and body-image depression has a mediating effect between online sexual objectification experience and physical activity.